Validation of the PARVA c.392A>T variant in a South African family with severe Arrhythmogenic Right Ventricular Cardiomyopathy - Kamuli, Stephen (Department of Medicine, 2017)
Introduction: Cardiomyopathy is an endemic disease in Africa that is a major contributor to the clinical syndrome of heart failure. The various forms of cardiomyopathies pose a great challenge in Africa for many reasons, including the difficulty of diagnosis and the scarcity of interventions such as heart transplantations in resource-poor environments. The aetiology of the cardiomyopathies had been unknown but various genetic abnormalities associated with cardiomyopathy have been unraveled. A previous whole exome sequencing project conducted in the United Kingdom (UK) had identified parvin alpha (PARVA) as a candidate gene in a South African family, ACM 8, with several members affected with arrhythmogenic right ventricular cardiomyopathy (ARVC). Hypothesis: We hypothesize that PARVA harbors novel genetic mutations that cause ARVC and other forms of cardiomyopathy. Aim: To screen the PARVA gene for mutations in a large panel of probands with ARVC and other cardiomyopathies and to validate the whole exome sequencing results obtained in the UK on a different sequencing platform. Methods and Results: We investigated the ACM 8 family with three affected individuals (two severely affected children and the mother) for whom the genetic cause of the disease was unknown. Genetic analysis was previously performed at Newcastle in the UK using whole exome sequencing on an Illumina platform. In this analysis, the PARVA c.392A>T variant was identified as a possible cause of ARVC in this family. We expanded on this work by using high resolution melt (HRM) analysis and Sanger sequencing to screen all the available ACM 8 family members to determine segregation of the PARVA c.392A>T variant within this family. We observed that the phenotypic variability seen within this family cannot be explained by the PARVA c.392A>T variant alone and called into question the causative role of PARVA within this family We also screened the cardiomyopathy cohort consisting of 180 probands diagnosed with ARVC, dilated cardiomyopathy (DCM), hypertrophic cardiomyopathy (HCM) and restrictive cardiomyopathy (RCM) in the Cardiovascular Genetics Laboratory. No definitive evidence of pathogenic PARVA variants was found any of the cardiomyopathy probands screened. We subsequently performed whole exome sequencing on this family to validate the UK findings ( Ion Torrent platform). We found that both affected individuals were homozygous for the PKP2 c.1162C>T mutation. PKP2 is a gene known to cause ARVC, and the c.1162C>T mutation has been described as a founder mutation for autosomal dominant ARVC families of Afrikaner decent in South Africa. Conclusion: While this study set out to validate the whole exome sequencing experiments conducted in family ACM 8 in the UK, we instead found the causal variant to be the previously reported PKP2 c.1162C>T mutation. We also explored the possibility of PARVA as a causal gene for ARVC but no pathogenic PARVA mutations were identified.